Shedding light on informal helpers’ willingness to intervene in psychological intimate partner violence: an application of Weiner’s attribution model - Chua, Xuan (Nanyang Technological University, 2022)
Psychological abuse is a form of Intimate Partner Violence (IPV) that has reached epidemic proportions, especially among young adults. While IPV remains largely unreported, victims tend to disclose the abuse to informal helpers who play a vital role in intervening. Using Weiner’s attribution model (1980) as a conceptual model, this study examined whether informal helpers’ willingness to intervene (WTI) in heterosexual psychological abuse can be explained by responsibility attributions and associated emotions towards the victim and perpetrator. It also explored how perpetrator-victim gender pairing (male-to-female abuse or female-to-male abuse) moderated the aforementioned relationships. 155 university-aged participants completed an online survey and were randomly assigned to read one of four vignettes depicting a scenario where a friend (male or female) disclosed a relationship conflict (with or without psychological abuse). Participants reported their perceived responsibility and emotions towards the two characters in the vignette and WTI in the situation. Results revealed a partial serial mediation of the positive association between abuse and WTI via perceived victim responsibility and sympathy for victim. A full serial mediation of the positive association between abuse and WTI via perceived perpetrator responsibility and anger towards perpetrator was also found. Perpetrator-victim gender pairing moderated the full serial mediation pathway between abuse and WTI through perceived perpetrator responsibility and anger towards perpetrator – male perpetrators of abuse were perceived as responsible while female perpetrators were not, resulting in anger towards only male perpetrators and, ultimately, WTI in male-to-female abuse but not female-to-male abuse. Implications and future research directions were discussed.